2017
DOI: 10.1016/j.jsha.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors, presentation, and in-hospital events of very young patients presenting with ST-elevation myocardial infarction

Abstract: Among young adults who use tobacco, there is a need for improved screening for risk factors. Earlier detection and treatment of dyslipidemia and hypertension could prevent acute cardiac events among individuals aged <40 years with multiple risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
1
21
1
1
Order By: Relevance
“…In our study, we found no relation in regards to HL history and none of our subjects had a history of familial combined hyperlipidaemia. However, patients requiring revascularization had lower HDL and higher TG levels, but had no statistically significant difference between LDL levels which was compatible with the majority of the studies (9,10,(29)(30)(31). Considering some patients were already on statin therapy we found that statin naïve patients had higher LDL and TG levels, and lower HDL levels in patients requiring revascularization.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, we found no relation in regards to HL history and none of our subjects had a history of familial combined hyperlipidaemia. However, patients requiring revascularization had lower HDL and higher TG levels, but had no statistically significant difference between LDL levels which was compatible with the majority of the studies (9,10,(29)(30)(31). Considering some patients were already on statin therapy we found that statin naïve patients had higher LDL and TG levels, and lower HDL levels in patients requiring revascularization.…”
Section: Discussionsupporting
confidence: 88%
“…Dyslipidaemia is found to be another cause of cardiovascular events among young population (9,10,16,(29)(30)(31)(32). In one study it was demonstrated that familial combined hyperlipidemia was associated with a 24-fold increased in acute coronary syndromes (8).…”
Section: Discussionmentioning
confidence: 99%
“…(18) Among young adults who consume cigarettes, there is a need for improved screening for risk factors. Earlier detection and treatment of dyslipidemia and hypertension could prevent acute cardiac events among subjects aged <40 years with multiple risk factors (19). In the group of older respondents (Group B), 62.5% had a reduced left ventricular ejection fraction (EFLV), and 37.5% of patients had normal EFLV.…”
Section: Discussionmentioning
confidence: 99%
“…По статистическим данным, ИБС у женщин до наступления менопаузы встречается значительно реже, чем у мужчин того же возраста. Пик заболеваемости приходится на возраст 65-75 лет, но в последние годы отмечено увеличение заболеваемости ИБС у фертильных женщин и молодых мужчин [5,6]. По данным проспективных исследований, ИБС болеют около 8-10 % мужчин в возрасте от 20 до 44 лет и 18-25 % в возрасте от 45 до 69 лет [7,8].…”
Section: Discussionunclassified